2023
DOI: 10.1038/s41598-023-41395-9
|View full text |Cite
|
Sign up to set email alerts
|

Remote psychophysical testing of smell in patients with persistent olfactory dysfunction after COVID-19

Marcela Martončíková,
Pavel Doležal,
Kamila Fabianová
et al.

Abstract: Olfactory dysfunction associated with coronavirus 2 (SARS-CoV-2) infection is in most cases transient, recovering spontaneously within a few days. However, in some patients it persists for a long time, affects their everyday life and endangers their health. Hence, we focused on patients with persistent loss of smell. The aim of this study was to evaluate olfactory dysfunction using a standardized test. Due to the pandemic, olfactory testing was performed online. Smell tests (Odorized Markers Test, OMT) were se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 63 publications
1
0
0
Order By: Relevance
“…The study also found a higher prevalence of hyposmia than anosmia (41.9% and 30.2% respectively). The higher prevalence of hyposmia when compared to anosmia (23.2% versus 18.3%) was also found in the study by [23].…”
Section: Discussionsupporting
confidence: 70%
“…The study also found a higher prevalence of hyposmia than anosmia (41.9% and 30.2% respectively). The higher prevalence of hyposmia when compared to anosmia (23.2% versus 18.3%) was also found in the study by [23].…”
Section: Discussionsupporting
confidence: 70%